ANALISIS TERHADAP PERJANJIAN JUAL BELI PROFORMA (STUDI KASUS PUTUSAN PENGADILAN NEGERI RABA BIMA NOMOR 47/PDT.G/2017/PN RBI) - Cindy Adinda Ratu; Arsin Lukman (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
The role of the Land Deed Making Officer is very important in making the land sale and purchase deed. In accordance with Government Regulation Number 37 of 1998 which has been changed to Government Regulation Number 24 of 2016 concerning Regulations for Land Deed Making Officials, PPAT is a public official who is authorized to make authentic deeds regarding certain legal actions regarding land rights or property rights. on the apartment unit. The problems raised in this research are the responsibility of the Land Deed Making Officer (PPAT) for the making of the Proforma Sale and Purchase Deed (formality) and the legal consequences arising from the Proforma Purchase (formality). The method used is normative research, the data sources used are primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques by means of literature study. The data analysis technique used qualitative methods. After the discussion, it was found that the Proforma Sale and Purchase (formality) did not meet the requirements for a valid agreement because it contained false causes. The Land Deed Making Official who makes the Proforma Sale and Purchase Deed (Formality) must be responsible for his actions and may be subject to written sanctions up to his dismissal from his position. And there are legal consequences of false data submitted to the Land Deed Making Official, which can be canceled or null and void by law. There is also the possibility of being sued for material damages by the aggrieved party in this case the Plaintiff on the basis of an unlawful act as regulated in Article 1356 of the Civil Code. Guidance and supervision of the profession of Land Deed Making Officials must also be strengthened so that cases of making Proforma Sale and Purchase Deeds do not recur.